NUTRITIONAL SUPPORT AND COMPLEMENTARY THERAPIES IN PCOS: CURRENT EVIDENCE AND FUTURE DIRECTIONS - Soniya. P,; Dr. Rajalakshmi, (The Bioscan, 2025)
Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder that significantly impacts reproductive and metabolic health in women of reproductive age. Globally, the prevalence of PCOS varies widely, with estimates ranging from 5% to 20%, affecting approximately 116 million women worldwide. In India, the prevalence ranges from 3.7% to 26%, highlighting a notable increase due to factors such as urbanization, changing lifestyles, and dietary habits. This paper reviews the pathophysiology, clinical manifestations, and management strategies for PCOS, focusing particularly on nutritional interventions and complementary therapies. Evidence suggests that a combined approach involving dietary adjustments, micronutrient supplementation, exercise, and psychological support can yield significant improvements in insulin sensitivity, metabolic health, and quality of life for patients. Increased awareness and research into the multifaceted nature of PCOS remain essential for establishing effective management protocols that address not only the physical symptoms but also the psychological impacts of this syndrome, thereby aiding public health efforts to combat the rising prevalence of PCOS in both global and Indian contexts.